Prosthetic valve thrombosis – association of genetic polymorphisms of VKORC1, CYP2C9 and CYP4F2 genes. Issue 6 (February 2019) - SR, Kalpana; G, Bharath; Jain, Simran; Moorthy, Nagaraja; Manjunath, Satvic C.; Christopher, Rita
Abstract : Abstract: Prosthetic Valve Thrombosis (PVT), in spite of the advances in the valve design and the material used, remains a serious complication of mechanical cardiac valve replacement. The factors influencing the development of PVT are: thrombogenicity of the valve, hemodynamics of the transprosthetic blood flow and ineffective anticoagulation. Genetic polymorphism of the genes VKORC1 (-1639 G > A and 1173 C > T), CYP2C9 (*2 & *3 alleles) and CYP4F2 (1347 G > A) are known to influence the anticoagulant dose-effect response. Since there has not been any earlier study on the direct influence of gene polymorphism on the development of PVT, we investigated into this association. Genotyping for the genes VKORC1, CYP2C9 and CYP4F2 was carried out by conventional PCR-RFLP method for 91 consecutive PVT patients. Subjects of our earlier study served as controls (n = 136). Female patients and patients with smaller prosthetic valve size were more prone to developing PVT (68%, n = 62). Patients bearing A allele of CYP4F2 1347 G > A polymorphism exhibited a fivefold increased risk of PVT (OR = 5.022 (1.39–18.04), P  = .013). G allele of VKORC1 when analyzed in combination of genotypes showed a fourteen fold increased risk for developing PVT (OR = 14.25 (5.52–36.77), P  = 0.001). CYP2C9 (*2&*3) gene polymorphism did not show any significant association with PVT (OR = 1.54 (0.128 – 18.82), P  = .731). Patients bearing A allele of CYP4F2 showed an increased risk of developing PVT in our case – control study.